(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
Storm surge phenomena are one of the most dangerous natural processes observed in the coastal zone of the sea. Dangerous extreme surge level fluctuations are observed at a wind speed of more than 15 m/s. The Sea of Azov has had a constant increase in its level over the past hundred years. During the period 1991–2016 216 cases of extreme level fluctuations were observed in the coastal zone of the sea. The level rise averaged 0.18 cm/year over the study period. Level rises cause significant destruction of the shores of the Sea of Azov, coastal abrasion reaches up to 6 m/year.